Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Jinka University - International Livestock Research Institute; Jinka University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Jinka University. On March 16, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Kusse Gudishe, President of Jinka University.